The Usage of What Country: A Critical Analysis of Legal Ethics in Transnational Legal Practice. Issue 2 (August 2019) - Arjona, César S.
Abstract: This article maintains that the standard conception of legal ethics – the so-called 'theory of amorality' – is highly dependent on context and cannot be consistently applied to transnational legal practice. After defining in some detail the basic tenets of the standard conception, I identify its main assumptions, namely, (i) that a legal relation is an agency relation in which both lawyer and client are individual moral agents, (ii) that such relation is connected to a litigation process, and (iii) that such relation takes place within the framework of a decently well-functioning rule of law system. Using as a paradigmatic example the BTC pipeline case– a set of contracts and international treaties signed by a consortium of private companies and several sovereign states during the first decade of the 21st century to regulate the building and operation of a transnational oil pipeline – I analyze one by one these three assumptions to conclude that they are at the very least highly problematic in the context of global legal practice. Additionally, I consider the counter-argument that a lawyer who moves beyond the standard conception is actually usurping the role of the judge, an argument that loses much of its appeal on the transnational context. In a brief concluding remark I inscribe these problems within the more general post-Westphalian paradigm shift in law and jurisprudence.